Low and High Voltage Ride-Through DFIG Wind Turbines Using Hybrid Current Controlled Converters - Mohseni, Mansour; Masoum, Mohammad Sherkat; Islam, Syed (ELSEVIER, 2011)
Doubly fed induction generators have been recognized as the dominant technology used in wind generation systems. However, this type of wind generator is very sensitive to the drop/rise in the supply voltage and without efficient “ride-through” strategy, continuous operation of DFIG may fail due to destructive overcurrents in the rotor winding or large overvoltages in the dc-link capacitor. This paper introduces a hybrid current control scheme, implemented in the rotor-side and grid-side converters of DFIG, to enhance low and high voltage ride-through capacities of DFIG-based wind turbines. The proposed control scheme is constituted of two switching strategies integrated with a supervisory control unit: standard PI current controllers for normal operating conditions and vector-based hysteresis current controllers for DFIG protection during severe voltage sag/swell conditions. Time-domain simulation studies are carried out to examine the effectiveness of the proposed ride-through strategy under various types of grid disturbances. It is shown that the proposed controller constrains the rotor current and dc-link voltage within the safety limits of DFIG and as a result, the wind generator can comply with the strict low/high voltage ride-through requirements stipulated by modern grid codes.